2007
DOI: 10.1103/physrevd.76.083516
|View full text |Cite
|
Sign up to set email alerts
|

Sterile neutrino-enhanced supernova explosions

Abstract: We investigate the enhancement of lepton number, energy, and entropy transport resulting from active-sterile neutrino conversion νe → νs deep in the post-bounce supernova core followed by reconversion νs → νe further out, near the neutrino sphere. We explicitly take account of shock wave and neutrino heating modification of the active neutrino forward scattering potential which governs sterile neutrino production. We find that the νe luminosity at the neutrino sphere could be increased by between ∼ 10 % and ∼ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 73 publications
3
69
0
Order By: Relevance
“…Similar discussions with sterile neutrinos can be found in Refs. [60,61,62]. Recently, a systematic study has been performed [63] based on a low mass supernova progenitor.…”
Section: Neutrino Oscillationsmentioning
confidence: 99%
“…Similar discussions with sterile neutrinos can be found in Refs. [60,61,62]. Recently, a systematic study has been performed [63] based on a low mass supernova progenitor.…”
Section: Neutrino Oscillationsmentioning
confidence: 99%
“…Alternatively, if the 7.1 keV sterile neutrino is only a component of the total dark matter, then a larger mixing angle could fit the observations [36,37]. There has already been much work on the effect of sterile neutrinos on the explosion mechanism and the r process in core-collapse supernovae [16,17,23,24,[38][39][40][41][42]. This was motivated by the anomalous results obtained at the Liquid Scintillator Neutrino Detector collaboration and other neutrino experiments that were better fit by (3+1) or (3+2) neutrino models.…”
Section: Introductionmentioning
confidence: 99%
“…Hidaka and Fuller [16,17] proposed that a sterile neutrino with the mass and mixing angle of a warm dark matter candidate might significantly alter the dynamics of supernovae. Using a one-zone collapse calculation, they found that a resonant conversion ν e → ν s could occur deep within the protoneutron star.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hidaka and Fuller 18,19 were the first to propose that sterile neutrinos could serve as an efficient neutrino energy transport mechanism in the supernova core. They used a one zone collapse calculation to study the resonant oscillations of a sterile neutrino with the mass and mixing angle of a warm dark matter candidate.…”
Section: -21mentioning
confidence: 99%